Biological characteristics and permissiveness to viruses of diploid kidney cells strain from the bat Nathusius’ pipistrelle (Pipistrellus nathusii Keyserling & Blasius, 1839; Chiroptera: Microchiroptera: Vespertilionidae) - O. S. Povolyaeva; S G. Yurkov; O. G. Lapteva; O. L. Kolbasova; A. A. Chadaeva; А. Yu. Kol'tsov; I. P. Sindryakova; M. E. Vlasov; S. P. Zhivoderov; A. V. Lunitsin (Вопросы вирусологии, 2021)
Introduction. Bats are an epidemiologically important natural reservoir of viruses of various taxonomic groups, including causative agents of especially dangerous infections of humans and animals. Considering the relevance of arbovirus infections, it seems advisable to study the spectrum of the sensitivity of cells derived from bats inhabiting and migrating on the territory of the Russian Federation to causative agents of vector-borne diseases of animals. The study aimed to obtain a diploid strain of cells from renal tissue of bats Pipistrellus nathusii and to investigate its biological characteristics, as well as to assess its permissiveness for bluetongue (BTV); Rift Valley fever (RVFV); lumpy skin disease (LSDV); rabbit myxoma (Myxomatosis cuniculi); rabbit, or Shope fibroma (RFV); African horse sickness (AHSV) and African swine fever (ASFV) viruses. Material and methods. There were 2 clinically healthy male individuals of P. nathusii who taken as donors of organs. To obtain diploid kidney cell culture strain and to study its properties, the level of the 6th passage was investigated by conventional cytological, virological, and molecular methods. The permissiveness of the obtained cell culture for BTV, RVFV, LSDV, Myxomatosis cuniculi, RFV, AHSV and ASFV was determined. Results. The formation of a confluent monolayer was observed after 72 hours, while the proliferation index was 2.7-3.3. The cell monolayer had been maintained without changing the medium for 45 days (observation period). The stability of the karyotype had been demonstrated in continuous subculturing at the 36th passage. The cell culture named «Diploid cell line Pipistrellus nathusii kidney», and its permissiveness to BTV, RVFV, LSDV and Myxomatosis cuniculi had been demonstrated. Discussion. The sensitivity of the strain to BTV and RVFV is consistent with the data on the identification of reovirus and RVFV in Egyptian fruit bats (Rousettus aegyptiacus), and its permissiveness for LSDV and rabbits myxoma virus is consistent with the results of detection of poxviruses in big brown bat (Eptesicus fuscus). Conclusion. A diploid kidney cell strain derived from P. nathusii was obtained and certified. Its permissiveness to BTV, RVFV, LSDV and rabbits myxoma viruses makes it possible to use this strain for isolation and studies of these viruses. Reproduction of the viruses in diploid kidney cells strain derived from P. nathusii living and migrating in the European part of the Russian Federation indicates their potential role in the epidemiology of significant infections, especially transmissible ones.